PK-PD Evaluation of Inhaled Microparticles loaded with Ciprofloxacin-Copper complex in a Rat Model of Chronic Pseudomonas aeruginosa Lung Infection. - Frederic Tewes; Barbara Lamy; Julian Laroche; Isabelle Lamarche; Sandrine Marchand (Elsevier, 2023)
The potential gain in efficacy of pulmonary administration over IV administration of some antibiotics such as ciprofloxacin (CIP) may be limited by the short residence time of the drug at the site of infection after nebulization. Complexation of CIP with copper reduced its apparent permeability in vitro through a Calu-3 cell monolayer and greatly increased its pulmonary residence time after aerosolisation in healthy rats. Chronic P. aeruginosa lung infections in cystic fibrosis patients result in airway and alveolar inflammation that may increase the permeability of inhaled antibiotics and alter their fate in the lung after inhalation compared to what was seen in healthy conditions. The objective of this study was to compare the pharmacokinetics and efficacy of CIP-Cu2+ complex-loaded microparticles administered by pulmonary route with a CIP solution administered by IV to model rats with chronic lung infection. After a single pulmonary administration of microparticles loaded with CIP-Cu2+ complex, pulmonary exposure to CIP was increased 2077-fold compared to IV administration of CIP solution. This single lung administration significantly reduced the lung burden of P. aeruginosa expressed as CFU/lung measured 24 h after administration by 10-fold while IV administration of the same dose of CIP was ineffective compared to the untreated control. This better efficacy of inhaled microparticles loaded with CIP-Cu2+ complex compared with CIP solution can be attributed to the higher pulmonary exposure to CIP obtained with inhaled CIP-Cu2+ complex-loaded microparticles than that obtained with IV solution.